Komunikasi Persuasif dalam Al-Qur'anTerkait Menafkahkan Harta - Musdhalifa, Musdhalifa; Aida, Nur (STID Al-Hadid, 2024)
God created humans with free will, so humans can choose to do good or bad. However, Allah, the Most Merciful, still guides humans to stay on the straight path. Using persuasive communication, Allah persuades Muslims to donate their wealth in the Way of Allah. This can be an example for preachers who want to persuade their followers to spend their wealth on religion. Using a descriptive qualitative method, this paper aims to describe persuasive communication in the Al-Qur'an regarding donating wealth. The data source is verses from the Al-Qur’an regarding spending on wealth. The result is that persuasive communication pays attention to God's position as the communicator and the psychology of Muslims as the communicant. The message uses an invitation sentence with lah particle, and an offer question. Persuasive communication techniques include: Pay of, promising a return from heaven. Fear arousing, fear of the torments of hell. Integration, reminding all wealth belongs to Allah. Swap, promises double the wealth. Simulated disinterest, emphasizing the limited time for charity. Don't ask if you ask which, comparing zakat with usury. Reassurance, explains God's credibility as a guarantor. Icing, tells the story of the condition of believers in the afterlife.